Dental Students’ Perception, Attitude and Willingness to Interact with Mental Illness Patients: A Multicentre Cross-Sectional Study - Malek, Mazarina Nurdini; Mat Yudin, Zainab; Abdul Hamid, Nor Faharina; Harun, Nor Asilah; Awang Bono, Suzanna; Awang Nawi, Mohamad Arif (Journal of Dentistry Indonesia, 2022)
Mental illness is a psychological impairment involving emotions, cognitions, and behaviors, and its prevalence is increasing worldwide. Dental students may encounter patients with underlying psychological problems during their training. Objective: To evaluate dental students’ perception, attitude, and willingness to interact with patients with mental illness. Methods: A multi-center cross-sectional study was conducted involving undergraduates at three dental institutions in Malaysia using an online self-administered questionnaire. Descriptive data analysis was conducted and statistical analysis using chi-square test was done for associations (p < 0.05). Results: The response rate was 63% (225); the majority of respondents were female (77.8%) and of Malay ethnicity (88.4%). Our study found that positive attitudes are independent of respondents’ sociodemographic profiles. No significant differences in attitudes were portrayed by gender, race, or history of mental illness. Our findings suggest that respondents’ place of study, gender, and previous encounter with mental illness are associated with willingness to interact with patients (p < 0.05). Conclusions: Dental students displayed positive attitudes and willingness to interact with patients with mental illness. However, to further improve students’ attitudes and enhance their readiness to interact with patients with mental illness, more mental health-related educational programs should be introduced in the dental curricula.